THE TIME FACTOR IN THE MODEL OF MARGINAL INCOME - A. K. Solodov (Стратегические решения и риск-менеджмент)
The subject of this paper is widely used in all economically developed countries, marginal approach. The purpose of this work is to study changes in the threshold of profitability in the time dynamics and identifying opportunities for application of the results obtained in the practice of financial managers.